Penggunaan Media Pembelajaran Berbasis Audio Visual Oleh Guru Geografi Pada Masa Pandemi Covid-19 Di SMA Negeri 5 Model Palu - Primananda, Riyanto; Hamid, Abdul (Jurusan Pendidikan IPS, Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako, 2021)
The aim in this study was to determine how the use of audio-based learning media by geography teachers and any factors that became supporters and inhibitors in the use of audio-visual media by geographic teachers during the Pandemic Covid-19 period in SMA 5 Palu models. This type of research is qualitative with a descriptive approach. The subjects in this study were 3 people geographic teachers. Data collection techniques used are observation, interviews and documentation. The results showed that the use of audio visual learning media had been geographic teachers during this pandemic period. The audio-visual media used is a learning video sourced from the internet through the YouTube channel, which is then uploaded on e-learning through the sman5palu.sch.id website. The supporting factors in the use of this audio-visual media are the availability of facilities, internet/wifi data quota, and also the availability of visual audio media on YouTube. And the inhibiting factor is the implication of the internet network that causes teachers to not be able to download, upload or play their audio visual media.